India-China boundary problem 1846-1947 - "Noorani, A.G" (New Delhi, 2011)
Boundary issues have always occupied a central focus in the relations between India and China. Highlighting the role of history, policy, and diplomacy, this book traces the origins and development of the India-China boundary problem during the British Raj. A.G. Noorani shows how British efforts to secure a defined boundary in the western sector began immediately after the creation of Jammu & Kashmir in 1846. However, in the eastern sector, such an exercise began only sixty-five years later, when a Chinese threat was perceived. Examining the role of the bureaucracy and diplomatic negotiations, the author presents a nuanced analysis of the treaties and conventions, as well as internal debates between British officials on conflicting policies. Breaking new ground, this book evaluates the relevance of the Indian Independence Act, 1947, and explains how the diplomatic history in the last hundred years shaped the boundary problem between India and China. What was a problem aggravated into a dispute that erupted in 1959. The central thesis is that history had direct relevance to the shaping of a sound policy. Based on archival research and unpublished material, this volume uses twenty-two appendices and fourteen maps to present a unique perspective on a long- standing problem.
Keywords: India foreign relations China